The clinical patterns of vitiligo "hospital-based study" in Makkah region, Saudi Arabia - M.I. Fatani; S.H. AlSharif; K.A. Alfif; A.S. Khan; W.A. Hussain; A.A. Banjar (Wolters Kluwer Medknow Publications, 2014)
Background: Little is known about the clinical patterns of vitiligo and its associations in Arab countries, particularly Saudi Arabia. Methods: We performed a retrospective review of 135 medical records of patient with vitiligo seen at the Hera Hospital, Makkah, Saudi Arabia between January 2010 and June 2013. Results: Of the 135 patients (mean age, 24.5 years), 91 (67.4%) were females. Twenty-six patients (25%) had a positive family history, 12.6% with associated thyroid disorders, 9.6% diabetes mellitus, 8.9% atopic dermatitis, 3.7% leukotrichia, and 2.2% alopecia areata. Sixty percent of patients had localized vitiligo, 37% generalized, 9.6% acrofacial, and 1.5% universal. The commonest site for the first vitiligo lesion was the face (28% of patients), whereas the commonest site at the time of diagnosis was the lower limb (51% of cases). The commonest topical treatment for localized vitiligo was tacrolimus (34.8%), whereas narrow band ultraviolet B (14%) had most commonly been prescribed for those with generalized vitiligo. Conclusions: The patients were predominantly females, with a large proportion having a positive family history. The mean age of onset of vitiligo in our study was 24.5 years. It was commonly associated with thyroid disorders. Localized vitiligo was the most prevalent type.